2017
DOI: 10.1038/srep40986
|View full text |Cite
|
Sign up to set email alerts
|

Low level of swiprosin-1/EFhd2 in vestibular nuclei of spontaneously hypersensitive motion sickness mice

Abstract: Susceptibility to motion sickness (MS) varies considerably among humans. However, the cause of such variation is unclear. Here, we used a classical genetic approach to obtain mouse strains highly sensitive and resistant to MS (SMS and RMS). Proteomics analysis revealed substantially lower swiprosin-1 expression in SMS mouse brains. Inducing MS via rotary stimulation decreased swiprosin-1 in the mouse brains. Swiprosin-1 knockout mice were much more sensitive to motion disturbance. Immunohistochemistry revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In a study we conducted previously we could show that swiprosin-1 was also expressed in the mouse brain, heart, stomach and kidney [25]. Here, we further found that swiprosin-1 was predominantly expressed in podocytes of the mouse glomerulus and was up-regulated in the kidney of 8-week-old diabetic mice.…”
Section: Introductionsupporting
confidence: 60%
“…In a study we conducted previously we could show that swiprosin-1 was also expressed in the mouse brain, heart, stomach and kidney [25]. Here, we further found that swiprosin-1 was predominantly expressed in podocytes of the mouse glomerulus and was up-regulated in the kidney of 8-week-old diabetic mice.…”
Section: Introductionsupporting
confidence: 60%
“…Male C57BL/6J mice (18-22 g) were purchased from Shanghai SLAC Laboratory Animal Co. The swiprosin-1-KO mice were generated as described previously (40). All mice were kept under an automated 12-hour dark-light cycle at a controlled temperature of 22°C ± 2°C and a relative humidity of 50%-60% with free access to standard dry diet and tap water (Shanghai Puluteng Biological Technology Co.).…”
Section: Methodsmentioning
confidence: 99%
“…Swiprosin-1-OE lentiviruses were produced as described previously (40). Briefly, recombinant lentiviruses expressing the CDS sequence (residues 54-776 in the murine swiprosin-1 cDNA sequence, GenBank NM_025994.3) of swiprosin-1 (LV-SWI) were produced by the Shanghai Innovation Biotechnology Co. RAW264.7 cells were transfected with LV-SWI or control lentiviruses without the swiprosin-1 CDS sequence (LV-GFP) for at least 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Swiprosin-1 desensitizes β-adrenergic receptors in the cultured adult ventricular rat cardiomyocytes, suggesting that it may play a key role in cardiac remodeling 21 , 22 . Swiprosin-1 expression in vestibular nuclei determines the susceptibility of mice to motion sickness 23 .…”
Section: Introductionmentioning
confidence: 99%